Meta Analysis: Factors Relating to Clean and Healthy Living Behaviors (CHLB) - Rima Permata Sari; Husaini Husaini; Eko Suhartono; Syamsul Arifin; Silvia Kristanti Tri Febriana (Jurnal Berkala Kesehatan, 2024)
Clean and healthy living behavior (CHLB) is a health program implemented in 1996. It is a social engineering to make as many agents of change from the community as possible to improve their quality of daily life for more clean and healthy. Riskesdas data for 2007, 2013, and 2018 state that CHLB in Indonesia has increased by only 28%, but has yet to reach the Ministry of Health's primary target, around 100% of Indonesians implement CHLB. This study aims to analyze health workers' associated knowledge, attitude, and role with clean and healthy living behaviors (CHLB).  This research uses a meta-analysis research design with a correlation meta-analysis research plan. Articles were taken from Google Scholar and PubMed databases. The 12 relevant articles according to the inclusion criteria using Review Manager 5.4. The result of the study showed knowledge is associated with CHLB with p=0.00001 and pOR value= 3.80; CI 95% 2.40-6.02, attitude is associated with CHLB with p=0.00001 and pOR value= 3.12; CI 95% 2.41-4.04 and role of health workers are associated with CHLB p=0.0001 and pOR value= 3.01; CI 95%= 1.93-4.72. Knowledge, attitude and role of health workers are related to clean and healthy living behavior (CHLB).